Tax Accounting in the Republic of Kazakhstan and Ways of its Improvement - BAIDYBEKOVA, Saltanat K.; BLEUTAEVA, Kulzhamal B.; ABDYKALIEVA, Zhupargul Sh.; TURYSBEKOVA, Raihan K.; SYZDYKBAEVA, Nurgul B.; BASTAUBAEV, Aslan K. (Journal of Advanced Research in Law and Economics, 2016)
Tax system reforming as a part of the country’s integration into the global market economy determined the need to improve the organization of tax accounting in enterprises. Thus, the purpose of this research is to determine the tax accounting problems in the Republic of Kazakhstan. In order to ensure the effectiveness of tax accounting and tax reporting of enterprises the authors developed recommendations related to the operational transition from accounting based on economic activities to tax accounting. The proposed model can improve reliability of information generated in all the company's accounting systems, reduce tax risks and improve the efficiency of tax accounting data usage to develop correct form of tax payments; it can also increase the efficiency of financial control activities of the enterprise. In this regard, research findings can be useful for employees, engaged in accounting and taxation in both domestic and foreign companies.